Intrauterine exposure to 17β-oestradiol (E2) impairs postnatal development in both female and male prostate in gerbil - Sanches, Bruno D.A.; Santos, Juliana M.; Zani, Bruno C.; Biancardi, Manoel F.; Santos, Fernanda C.A.; Góes, Rejane M. [UNESP]; Vilamaior, Patricia S.L. [UNESP]; Taboga, Sebastião R. [UNESP] (Elsevier, 2017)
We employed histological techniques to assess the effects of intrauterine exposure to different dosages of E2 on male and female Mongolian gerbils on the postnatal development of the prostate. E2 promotes alterations this gland branches in the female, but not in males, even at low dosage, at higher dosages, acini of altered aspect are verified in the male and female prostate, as well as a decrease in branching number, reduced cell proliferation and staining for FGF10, simultaneously to the increased labelling for TGFβ1, which may account for alterations on branching of the prostate. The sensitivity of the female prostate to intrauterine exposure to E2, which can reflect the E2 dependence of female prostate development. This becomes alarming in view of the occurrence of prostate in female of several mammals and including women, and the possibility that low E2 dosage exposures considered safe to males provoke developmental alterations in female prostate.
Keywords: AR; CD34; E2; Environment; ESR1; ESR2; Female prostate; FGF10; Intrauterine exposure; Sex variations; TGFβ1